Além do lixo: poder, motivação, estratégias e rede de relações na dinâmica de interação entre catadores de materiais recicláveis - Almeida, Rosimery Alves de (2024)
This thesis sheds light on the complex interdependence of social relations in liquid and advanced modernity, which are based on exchanges that, in turn, are grounded in relationships of influence supported by power bases enabling individuals to exert power. The study seeks to understand the impact of relationship networks, motivations, power bases, and strategies in interactions among waste pickers. To this end, the research was conducted using Raven's theoretical model (1992), employing social network analysis and a qualitative approach in two exploratory-descriptive phases. Field research involved 152 waste pickers from Sousa, Marizópolis, and Cajazeiras/PB, through semi-structured interviews and content analysis. In the first phase, mapping results revealed a network with low-density and fragile connections, predominantly consisting of women, Black and mixed-race individuals, and elderly persons, exacerbated by illiteracy and extreme poverty. Additionally, findings from the second phase explored four categories of analysis related to the theoretical model, uncovering elements of the network's structure and dynamics, which appeared moderately centralized with disparities where connectivity or centrality did not necessarily imply power. However, different levels of closeness affected the network, and mediators in integration could strengthen relationships. Consequently, waste pickers occupying strategic positions influence interaction dynamics through varied motivational types. Power bases, not limited to individual influence, are socially constructed phenomena adapting to complexities in urban environments, thereby sustaining these relationships. Lastly, strategies adopted by waste pickers underscore the diversity in theoretical approaches to these interactions. Limitations included the absence of a reliable database on the exact number of organizations and waste pickers in the studied municipalities and difficulties in accessing a larger sample due to informal and dispersed work. Recommendations include replicating the study with more waste pickers across different municipalities for a broader investigation and insights in to other actors in the recycling chain. The study achieved its goals, yielding robust and applicable results that can inform future research. Thus, the thesis argues that relationship networks, motivations, power bases, and strategies significantly influence the dynamics of interactions among waste pickers, contributing not only to understanding their influence and power but also to theoretical, practical, and managerial advancements, and policymaking.